1997
DOI: 10.2307/2533573
|View full text |Cite
|
Sign up to set email alerts
|

Validity and Efficiency of Approximation Methods for Tied Survival Times in Cox Regression

Abstract: Survival-time studies sometimes do not yield distinct failure times. Several methods have been proposed to handle the resulting ties. The goal of this paper is to compare these methods. Simulations were conducted, in which failure times were generated for a two-sample problem with an exponential hazard, a constant hazard ratio, and no censoring. Failure times were grouped to produce heavy, moderate, and light ties, corresponding to a mean of 10.0, 5.0, and 2.5 failures per interval. Cox proportional hazards mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
89
0
10

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 164 publications
(100 citation statements)
references
References 8 publications
1
89
0
10
Order By: Relevance
“…But it has larger biases than the EM for normal and exponential covariate distributions, especially for larger ties, similar to RB procedure. Our simulation study shows that Efron procedure has the best performance of the existing methods dealing tied survival data, which is consistent with the findings of Hertz- Picciotto and Rockhill (1997). Compared with the EM procedure, Efron procedure works better with binary and uniform covariate distributions.…”
Section: Simulation Studiessupporting
confidence: 87%
See 2 more Smart Citations
“…But it has larger biases than the EM for normal and exponential covariate distributions, especially for larger ties, similar to RB procedure. Our simulation study shows that Efron procedure has the best performance of the existing methods dealing tied survival data, which is consistent with the findings of Hertz- Picciotto and Rockhill (1997). Compared with the EM procedure, Efron procedure works better with binary and uniform covariate distributions.…”
Section: Simulation Studiessupporting
confidence: 87%
“…These distributions account for some of the practical situations where covariates are binary, approximately uniformly distributed, symmetrical or skewed. Here we choose the binary covariate as .6931×Bernoulli (1, .7), which results in a hazard ratio of 2 in the two sample situation when β = 1, a scenario considered by Hertz-Picciotto and Rockhill (1997).…”
Section: Simulation Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Validation studies of time to pregnancy have shown that the recall of time to pregnancy seems accurate even over longer time periods (12,14,17,18). We asked about time to pregnancy in four categories in order to assist the women and accepted a possible minimal loss in precision estimates of the fecundability ratio (27).…”
Section: Discussionmentioning
confidence: 99%
“…Those associated with time to loss of colonization in univariate analyses (2-sided P Ͻ 0.20) were included in the multivariable models and maintained in the final models when their HR estimates remained statistically significantly associated (2-sided P Ͻ 0.05) with loss of colonization using a manual backward stepwise procedure, yielding the final adjusted models. All univariate and multivariable models were adjusted for center and fitted with the Efron method for handling ties (23). Interactions between the strain's methicillin resistance phenotype and all the covariates remaining in the final model of loss of S. aureus colonization were systematically evaluated.…”
Section: Fig 1 Flowchart Of the Study Populationmentioning
confidence: 99%